Modo 302 product shots. - Ablan, Dan (3D Garage.com : AGA Digital Studios, 2008)
"Learn to create realistic looking products in modo 302! Volume 1 of this video training explored creating bottles and containers good for soap, shampoo, lotions, and concentrated on lighting and sets. In volume two, you'll increase your learning with modeling packages, bags, and intricate spray bottles. In nearly 3 hours of video training, you'll learn to use enhanced modeling techniques, connection operations, image mapping with masking, how to make wrinkles, UV Mapping, studio lighting, and more."--Resource description page.